Protocol for developing a Consolidated Checklist for Reporting Mixed Methods Research (CORMIX) using modified Delphi - Myriam Jaam; Ahmed Awaisu; Derek Stewart; Banan Mukhalalati; Ahsan Sethi; Marwa Elshazly; Abrar Abdelrahman; Muhammad Abdul Hadi (PLoS ONE, 2025)
Background Mixed methods research has gained popularity across healthcare and social sciences. However, inconsistent, and inadequate reporting remains a concern, hindering the assessment and utilization of mixed methods studies. Comprehensive easy-to-use mixed methods reporting standards are lacking. This protocol outlines the development of the COnsolidated Checklist for Reporting Mixed Methods Research (CORMIX) to address this gap. Methods Following the EQUATOR Network guidelines, the protocol involves conducting a scoping review to identify potential checklist items from current reporting guidelines and existing literature. This will be followed by executing a modified Delphi with a panel of experts in mixed methods research for further refinement through consensus. The modified Delphi will include ≥40 purposively selected experts who have extensively utilized and published mixed methods research. A questionnaire compiling literature-derived reporting items will be validated and distributed in successive rounds until consensus is reached on all items. Consensus is defined as ≥ 85% of experts agreeing on the inclusion of an item. Following the finalization of the checklist, a user guide and justification document will be completed. Discussion This rigorous development process conforms with EQUATOR Network standards for health reporting tools. CORMIX has the potential to enhance the quality, consistency, and transparency of mixed methods reporting. Clear reporting is essential for assessing validity, replicating studies, and enabling synthesis and application of mixed methods evidence. The protocol is currently registered with the EQUATOR network: CORMIX – COnsolidated Checklist for Reporting Mixed-Methods Research.